Spatio-temporal evolution analysis of coupling coordination of green finance, digital economy, and carbon emission intensity in the Yangtze River Economic Belt - Sui, Yue-Yue; Zhang, Xing-Fu (Frontiers in Environmental Science, 2025)
IntroductionUnder the current situation of increasingly severe environmental problems, carbon emission intensity (CEI) has become an essential indicator for evaluating the degree of environmental pollution, and sustainable development has become an eternal issue pursued by human beings. Along with the deepening of the concept of green sustainable development, green finance (GF) and digital economy (DIEC) have gradually become environmentally friendly and reliable tools that play an active role in controlling carbon emissions. Therefore, to promote sustainable economic development, it is necessary to promote GF, DIEC, and CEI in an integrated way, and there are relatively few studies on the synergistic promotion of these three aspects.MethodsUsing the entropy method, the coupling coordination degree model (CCDM), and the spatial analysis method, this study thoroughly examines the spatio-temporal pattern of the coupling and coordination of GF, DIEC, and CEI in the Yangtze River Economic Belt using panel data from 11 provinces in the region from 2013 to 2022.ResultsThe findings demonstrate that: (1) The Yangtze River Economic Belt’s general extent of GF and DIEC advancement is increasing, and the DIEC’s level exhibits a pattern of a declining gradient from the downstream to the upstream areas. (2) The Yangtze River Economic Belt’s CEI is on the decline, with the upstream region having a higher CEI than the middle and downstream regions. (3) Although there is regional diversity, the Yangtze River Economic Belt’s three systems exhibit a growing trend in connection and coordination degree. (4) The Yangtze River Economic Zone shows a declining trend in the spatial difference in the coupling coordination degree (CCD) of the three systems(overall Gini coefficient reduced by 31% from 2013 to 2022), with the upstream showing the smallest discrepancy and the downstream showing the biggest. The discrepancy between upstream and downstream is mainly caused by the different economic structures as well as the levels of progress of the two regions. The source of the discrepancy is mainly interregional.DiscussionThis paper puts forward some suggestions in light of the advancement status of the three systems in the region, hoping that it can provide a reference basis for the sustainable development of the region.